Cultural Barriers of Masalembu Island Fisherman Children in Continuing School - Habibi, Habibi; Syabana, Rizal Andi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
Masalembu Island is one of the outer islands of the sea area of Sumenep Regency. Most of the population are fishermen from three main tribes: Madurese, Bugis, and Mandar. One of their big problems in education is the large number of children who do not continue their education, either to high school or university level. This qualitative research aims to explore the cultural barriers for the children of Masalembu Island fishermen that cause them not to continue school. The snowball technique produced six participants, namely three children of fishermen, two heads of fishing families, and one teacher. Researchers used semi-structured interviews and observation methods to collect data, which was then analyzed using five techniques carried out iteratively: data collection, data organization, reading and making memos, description and classification, and interpretation. Analysis of research findings produced five main themes regarding the cultural barriers for fishermen's children to continue school: children as economic support for the family, views on the role of women, juvenile delinquency, the passive role of parents, and failure of college graduates to meet cultural expectations. In short, the cultural barriers of Masalembu Island fishermen children in continuing school are related to the mismatch between children's roles at school and their cultural roles in the family.